A device for dried blood microsampling in quantitative bioanalysis: overcoming the issues associated blood hematocrit. (April 2015) - Spooner, Neil; Denniff, Philip; Michielsen, Luc; De Vries, Ronald; Ji, Qin C; Arnold, Mark E; Woods, Karen; Woolf, Eric J; Xu, Yang; Boutet, Valérie; Zane, Patricia; Kushon, Stuart; et al.
Aims: A cross-laboratory experiment has been performed on a novel dried blood sampler in order to investigate whether it overcomes issues associated with blood volume and hematocrit (HCT) that are observed when taking a subpunch from dried blood spot samples.Materials & methods: An average blood volume of 10.6 μl was absorbed by the samplers across the different HCTs investigated (20–65%).Results: No notable change of volume absorbed was noted across the HCT range. Furthermore, the variation in blood sample volumes across six different laboratories was within acceptable limits.Conclusion: The novel volumetric absorptive microsampling device has the potential to deliver the advantages of dried blood spot sampling while overcoming some of the issues associated with the technology.